Adjustment within the euro. The difficult case of Portugal - Blanchard, Olivier (2018)
In the second half of the 1990s, the prospect of entry in the euro led to an output boom and large current account deficits in Portugal. Since then, the boom has turned into a slump. Current account deficits are still large, and so are budget deficits. This paper reviews the facts, the likely adjustment in the absence of major policy changes, and examines policy options.